"HUBUNGAN ANTARA KESENGAJAAN TERHADAP PERTANGGUNGJAWABAN PIDANA DALAM KASUS KECELAKAAN LALU LINTAS DI JALAN YANG MENYEBABKAN HILANGNYA NYAWA ORANG SESEORANG" - M Budi Hendrawan; Alvi Syahrin; Budiman Ginting; Mahmud Mulyadi (USU LAW JOURNAL, 2015)
ABSTRACT   Traffic is also known with the intent and negligence. Most formulation of a criminal offense, the element of intent or called by opzet is one of the most important elements. Relation to the element of intent, then when in a formulation of criminal acts are acts intentionally or commonly referred to opzettelijk, then this master element intentionally or include all the other elements that are placed behind and had to be proven. Relation to traffic accidents is in terms of motor vehicle driver negligent in maintaining the safety of themselves and others. This study aims to identify and analyze the relationship with punishment deliberate, intentional element which can be applied in sentencing traffic accidents, and the element of punishment in a traffic accident that resulted in the death of the element of intent. Keywords : traffic accidents, punishment deliberate